Altered Functional Connectivity of Insular Subregions in Type 2 Diabetes Mellitus - Zhang, Dongsheng; Wang, Man; Gao, Jie; Huang, Yang; Qi, Fei; Lei, Yumeng; Ai, Kai; Yan, Xuejiao; Cheng, Miao; Su, Yu; Lei, Xiaoyan; Zhang, Xiaoling (Frontiers in Neuroscience, 2021)
Diabetes-related brain damage can lead to cognitive decline and increase the risk of depression, but the neuropathological mechanism of this phenomenon remains unclear. Different insula subregions have obvious functional heterogeneity, which is related to many aspects of type 2 diabetes mellitus (T2DM)-related brain damage. However, little is known about changes in functional connectivity (FC) in insular subregions in patients with T2DM. Therefore, we aimed to investigate FC between different insula subregions and clinical/cognitive variables in patients with T2DM. Fifty-seven patients with T2DM and 55 healthy controls (HCs) underwent a neuropsychological assessment and resting-state FC examination. We defined three insula subregions, including the bilateral dorsal anterior insula (dAI), bilateral ventral anterior insula (vAI), and bilateral posterior insula (PI). We examined differences in FC between insula subregions and the whole brain in patients with T2DM compared with HCs. A correlation analysis was performed to examine the relationship between FC and clinical/cognitive variables. Compared with HCs, patients with T2DM showed significantly decreased FC between the dAI and the right inferior frontal gyrus, right superior/middle temporal gyrus, right hippocampus, and right precentral gyrus. FC between the vAI and the right supramarginal gyrus, as well as the PI and the right precentral/postcentral gyrus, was reduced in the T2DM group compared with the control group. In the T2DM group, we showed a significant negative correlation between glycated hemoglobin concentration and FC in the dAI and right hippocampus (r = −0.427, P = 0.001) after Bonferroni correction. We conclude that different insular subregions present distinct FC patterns with functional regions, and abnormal FC in these insular subregions may affect cognitive, emotional, and sensorimotor functions in patients with T2DM.